Upregulation of lncRNA AGAP2-AS1 is an independent predictor of poor survival in patients with clear cell renal carcinoma - Gao, Lei (Oncol Lett, 2020)
Long non-coding RNA (lncRNA) AGAP2-AS1 has been reported to be a potential biomarker for a variety of cancer types, while its function in clear cell renal carcinoma (ccRCC) has not yet been fully determined. The current study aimed to determine the value of lncRNA AGAP2-AS1 in ccRCC based on The Cancer Genome Atlas (TCGA) database. The association between AGAP2-AS1 expression and associated clinical characters were analyzed using the Wilcoxon signed-rank test and logistic regression. The diagnostic value of AGAP2-AS1 expression in ccRCC tissue was assessed using receiver operating characteristic (ROC) curve analysis. Clinicopathological characteristics associated with overall survival in patients with TCGA were analyzed using Cox regression and the Kaplan-Meier method. Gene set enrichment analysis (GSEA) was also performed to assess the biological function of AGAP2-AS1. The results demonstrated that increased expression of AGAP2-AS1 in ccRCC was significantly associated with male, T3/T4, lymph node metastasis, distant metastasis and high tumor stage (III/IV; all, P<0.05). The area under the ROC curve (normal vs. all tumors) was revealed to be 0.891. Kaplan-Meier survival analysis indicated that ccRCC with high lncRNA AGAP2-AS1 exhibited a worse prognosis compared with low AGAP2-AS1 (P<0.001). The univariate analysis revealed that high expression of AGAP2-AS1 was significantly associated with poor overall survival [hazard ratio (HR). 1.85; 95% confidence interval (CI), 1.48–2.33; P<0.001). Multivariate analysis revealed that AGAP2-AS1 remained independently associated with overall survival, with a HR of 1.57 (CI, 1.21–2.03; P<0.01). GSEA outcome demonstrated that stromal stimulation, angiogenesis, epithelial to mesenchymal transition, basal cell carcinoma, ECM receptor interaction and the Notch signaling pathway were differentially enriched in the AGAP2-AS1 high expression phenotype. Therefore, the high expression of AGAP2-AS1 may be an independent predictor of poor survival in patients with ccRCC.